AB0032 Upregulation of CD64 expression on monocytes in patients with active adult-onset still's disease: a possible biomarker for assessing disease activity. (15th June 2017) - Oguro, E; Shimizu, T; Kikuchi-Taura, A; Tsuji, S; Okita, Y; Shigesaka, M; Matsuoka, H; Nii, T; Teshigawara, S; Kudo-Tanaka, E; Harada, Y; Matsushita, M; et al.
Abstract : Background: Adult-onset Still's disease (AOSD) is a systemic inflammatory disease of unknown etiology. Overproduction of multiple inflammatory cytokines and subsequent hyperactivation of monocytes/macrophages are prominent characteristics of AOSD. However, there are no convenient and precise methods for evaluating monocyte/macrophage activation in AOSD. We previously reported that monocyte CD64 (mCD64) expression could be quantitatively measured by flow cytometry and its expression was tightly correlated with the activity of systemic lupus erythematosus. Objectives: We examined the association between mCD64 expression and AOSD disease activity. Methods: This was a prospective, single-center, observational study conducted between January 2013 and December 2016. Eleven active AOSD patients who fulfilled the Yamaguchi's criteria for AOSD and had the modified Pouchot score of ≥2 were enrolled. The mCD64 expression levels were quantitatively measured by flow cytometry and individually assessed both before (Pouchot score ≥2) and after treatment (score 0). Other disease-related laboratory data, such as C-reactive protein, ferritin, and white blood cell count, were simultaneously measured. As a control, 16 active systemic lupus erythematosus (SLE) patients (SLE disease activity index ≥6), 22 active rheumatoid arthritis (RA) patients (disease activity score with 28-joint counts >3.2), and 20 healthy controls (HC) (female, 55%; mean age, 38.7±9.1 years) were enrolled. Statistical analysis was performed by the Mann-Whitney and Wilcoxon-paired tests. Results: The median mCD64 expression levels were 73, 339 [interquartile range (IQR), 45, 861–88, 181] and 16, 443 (IQR, 45, 891–88, 181) molecules/cell before and after treatment, respectively. Thus, mCD64 expression levels were significantly decreased during the inactive phase compared with those in the active phase in AOSD (p=0.0001). The mCD64 expression levels were significantly higher in patients with active AOSD than in those with active SLE [34, 648 (IQR, 44, 204–24, 657) molecules/cell, p=0.001], active RA [25, 167 (IQR, 35, 778–22, 301) molecules/cell, p<0.0001], and in HC [14, 174 (IQR, 13, 413–17, 774) molecules/cell, p<0.0001]. Conclusions: These results suggest that mCD64 expression levels are highly upregulated in AOSD and tightly correlated with disease activity. The mCD64 expression level may be a useful biomarker for assessing the disease activity of AOSD. References: Rau M, et al. J Rheumatol. 2010 Nov;37(11):2369–76. Kikuchi-Taura A, et al. Lupus. 2015 Sep;24(10):1076–80. Pouchot J, et al. Medicine. 1991;70:118–36. Disclosure of Interest: None declared